Using satellite imagery to estimate abundance of Cumberland Sound beluga whales (Delphinapterus leucas) in 2021 - Sherbo, Bryanna A. H.; Belanger, Amanda M.; Charry, Bertrand; Watt, Cortney A. (Frontiers in Marine Science, 2024)
The Cumberland Sound beluga whale (Delphinapterus leucas) population inhabits Cumberland Sound on the southeast side of Baffin Island, Nunavut. The population is listed as threatened under the Species at Risk Act. The last abundance estimate from an aerial survey was estimated at 1,381 (95% CI: 1,270-1,502) beluga whales in 2017 for an area covering 12,485 km 2 . Since then, satellite imagery has been used as a remotely based non-invasive method to monitor these whales. Very High Resolution (VHR) satellite imagery covering 9,690 km² of water was collected from Cumberland Sound from August 30 to September 7, 2021, during the ice free season. Readers with previous imagery analysis experience analyzed the images and identified 704 certain detections. Abundance estimates were corrected for availability bias for whales that were too deep to be detected in the imagery (>2m). We present a total estimate of 1,690 (CV = 0.16; 95% CI: 1,241-2,301) beluga whales in Cumberland Sound (22,663 km 2 ). This estimate covers a larger area and estimates a higher abundance than the 2017 aerial survey. Regular population abundance assessments are essential for understanding population dynamics and trends and we have shown here that satellite imagery is a comparable method to aerial surveys for estimating abundance.